Sensitivitas Etis Mahasiswa Atas Penggelapan Pajak - Nurma Risa (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
This study aims to prove that there is a difference of perception about ethics on tax evasion in UNISMA Bekasi students, based on selected study program and gender. The sample of this research is the students who have fulfilled the subject of taxation, at the Faculty of Economics (FE) and Faculty of Social and Political Sciences (FISIP). Using independent t-test, the results showed that there was no significant difference of perception about tax evasion ethics between FE and FISIP students. But significant differences the perception of tax evasion ethics occur between accounting and management students at FE. Significant differences also did not occur between male and female students